Barriers and Challenges to Telecardiology Adoption in Malaysia Context - Kee-Jiar Yeo; Lina Handayani; Haikal Satria; Shih-Hui Lee; Chia-Keat Yap (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Mainly in infrastructure deficient communities, telecardiology is considered as a complement to insufficient cardiac care. Telecardiology can reduce travelling and waiting time, enables information sharing in shorter time and facilitate care in rural and remote areas. A qualitative study examined the perspectives of health care providers: cardiologist and general physician and health care service receivers: patient and public towards telecardiology adoption. The barriers in telecardiology adoption were identified in this paper. It includes practicality of telecardiology, the need of education for staffs and administrators, ease of use, preferred face-to-face consultation, cost and confidentiality. Improvements can be done by the implementers based on this study in order to promote telecardiology successfully in Malaysia.